Role of bone marrow aspiration and biopsy in evaluation of leucoerythroblastic blood picture (Panacea Journal of Medical Sciences, 2022)
Background: Leucoerythroblastosis was considered as a circulating expression of haematological and non-haematological malignancies. However many benign conditions are also associated with leucoerythroblastosis such as hemolytic anaemia, marked infections and congestive cardiac failure, etc. So the study was performed to determine the various causes of leucoerythroblastic blood picture on bone marrow examination.Materials and Methods: The current retrospective diagnostic analytical study was performed in the hematology section of post graduate department of pathology over a period of one year. 80 patients with leucoerythroblastic picture on peripheral blood film (PBF), who were subjected to bone marrow aspiration and/or biopsy were included in the study. The findings were documented on a predefined performa and results tabulated.Majority of cases were seen in 21-30 years age group (25%) with male to female ratio of 1.1:1. Non-neoplastic disorders accounted for majority of cases (65%) while neoplastic lesions were seen in 35% cases. Megaloblastic anaemia was the commonest neo-neoplastic etiology while acute leukemia was the commonest neoplastic disorder in the present study.Conclusions: Leucoerythroblastosis represents disordered marrow function and is reflected in PBF. Bone marrow aspiration and biopsy help in establishing early diagnosis and management of the underlying condition.